2003
DOI: 10.1021/jf034505v
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Patulin Toxicity on Rumen Microbial Fermentation by SH-Containing Reducing Agents

Abstract: Patulin, a toxic fungal metabolite, negatively affects rumen fermentation. This mycotoxin has also been associated with intoxication cases in cattle. This study investigates the use of SH-containing reducing compounds to prevent patulin's negative effects on the rumen microbial ecosystem. The effect of 50 microg/mL patulin on the fermentation of alfalfa hay was measured in batch cultures with and without reducing agents. Sulfhydryl-containing cysteine and glutathione prevented the negative effects of the toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 19 publications
(24 reference statements)
2
34
0
1
Order By: Relevance
“…5d). This finding was in agreement with the report that glutathione is a scavenger of patulin and can reduce the toxicity of patulin towards rumen fermentation (Morgavi et al 2003). It has been reported that S. cerevisiae is highly tolerant to oxidative stress (Jamieson 1998).…”
Section: Discussionsupporting
confidence: 93%
“…5d). This finding was in agreement with the report that glutathione is a scavenger of patulin and can reduce the toxicity of patulin towards rumen fermentation (Morgavi et al 2003). It has been reported that S. cerevisiae is highly tolerant to oxidative stress (Jamieson 1998).…”
Section: Discussionsupporting
confidence: 93%
“…Total lactic acid concentration was assessed in rumen fluid using an enzymatic commercial kit (ENZY + DL Lactic acid, EZA891 + , Biocontrol, Lyon, France) in a 96-well microtitre spectrophotometer. VFA analyses were performed as previously described (Morgavi et al, 2003) on a gas chromatograph CP9002 (Chrompack) and using crotonic acid as internal standard.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Seeling, Dänicke, et al (2006) describe, for example, an increased crude protein degradation and a lower molar percentage of propionate in the rumen when Fusarium-contaminated wheat was fed to dairy cows. Certain mycotoxins such as, for example, patulin affect the rumen fermentation (Morgavi et al 2003) and decrease acetic acid production and protein synthesis (Escoula 1992).…”
Section: Conversion Of Mycotoxins By the Rumen Floramentioning
confidence: 99%